Donor dilemmas in a fragile state: NGO-ization of community healthcare in Guinea-Bissau. (17th December 2018) - Baldursdóttir, Sigríður; Gunnlaugsson, Geir; Einarsdóttir, Jónína
ABSTRACT: There is increased emphasis on donor engagement in the world's poorest and most fragile states, but aid modalities tend to differ depending on the recipient countries' governance. In fragile states, donors often bypass governments and collaborate with non-state development actors (NGOs) to prevent aid capture, improve effective delivery and increase effectiveness. Based on ethnographic fieldwork over 20 months in 2009–2012, the aim of this paper is to explore the role of NGOs in community-based primary healthcare vis-à-vis the Ministry of Health in Guinea-Bissau. Revitalization of Guinea-Bissau's formerly extensive community healthcare services was initiated in 2010. The Ministry of Health, in charge of its implementation, emphasized ownership, harmonization and alignment that created tension with NGOs. However, as a result of a military coup in 2012, donors bypassed the Ministry and gave NGOs a central role. Through the voices of stakeholders, this paper outlines donors' dilemmas in a situation of state fragility. They found NGO-ization reasonable to protect funds and secure implementation while some worried that it might counteract alignment, harmonization, ownership and sustainability. The paper argues that aid to the health sector in fragile states needs to be long-term and predictable.